Modelling and managing 3D spatial objects - Mohamad Zulkifli, Siti Nur Awanis; Abdul Rahman, Alias (2008)
Currently, variety of software is already capable of handling a wide range of spatial problems, beginning with approaches for describing spatial objects to quite complex analysis and 3D visualisation. However, increasing number of applications need more advanced tools for representing and analyzing the 3D world. Among all types of systems dealing with spatial information, GIS has proven to be the most sophisticated system that operates with the largest scope of objects (spatial and semantic), relationships and provide means to analyze them. However, how about 3D GIS? It is the aim of this paper to find the answer by analyzing the available software. A 3D case study performed in Oracle Spatial and MicroStation Bentley Map provides knowledge about the 3D functionality offered by commercial systems. At the end, the paper addresses some of the issues and problems involved in developing such a system and recommends directions for further research.